DETERMINASI YANG MEMPENGARUHI AUDIT REPORT LAG (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023) - Mellisa, Sefi; Setiawati, Erma (ITB AAS Indonesia Surakarta, 2025)
This research is about the determination that affects audit report lag. The object of this study is a manufacturing company in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2020-2023 period. The data used is secondary data in the form of the company's annual report published by the official www.idx.co.id website. The sample selection method used purposive sampling and 59 companies were obtained in accordance with the criteria of the 4-year research period so that 236 samples were obtained in this study. This research method uses multiple linear regression and uses the help of the SPSS version 27 program. The results of this study show that profitability, solvency, company size, company age, and auditor reputation affect audit report lag.